Preface to the special section on algorithms and architectures for real-time control - Ruano, Antonio (2013)
Rapid developments in microelectronics and computer science continue to fuel opportunities for real-time control engineers. These openings arise from drivers such as ever-increasing system complexity and sophistication, environmental legislation, economic competition, safety and reliability. These are typical of the themes that were highlighted at the IFAC Workshop on Algorithms and Architectures for Real-Time Control (AARTC '97).